On the peculiarities of succession in Uzbek literature - G’afforov Nodir Nasriyevich; Boltayeva Iqbol Tadjibayevna (International Journal on Orange Technologies, 2021)
The centuries-old huge and inexhaustible treasure of Uzbek literature has served as a basis for the emergence of the artistic potential of countless famous prose writers, playwrights and poets. This article examines the problem of succession in fiction, its role in the development of any national literature, the means and methods of literary succession in the example of Uzbek literature, which is studied in depth, seriously and extensively in world literature. The article can be used by philologists who deal with various issues of fiction and a wide range of readers interested in art.